Serum ghrelin levels in patients with Behcet's disease - Erden, Ilker; Ucak, Haydar; Demir, Betul; Cicek, Demet; Dertlioglu, Selma Bakar; Aydin, Suleyman; Ozturk, Savas (Termedia Publishing House Ltd, 2016)
Introduction: Behcet's disease (BD) is a chronic, relapsing, systemic vasculitis of unknown etiology. Aim: To measure serum ghrelin levels in BD patients and healthy controls and to investigate its association with metabolic syndrome (MetS). Material and methods: Thirty BD patients and 30 healthy individuals were enrolled in the study. Ghrelin levels were measured in blood samples using ELISA. Results: The mean serum ghrelin level in BD patients (28.57 +/- 14.04) was significantly lower compared to healthy controls (40.72 +/- 23.21) (p = 0.01). The mean serum ghrelin level in BD patients who had MetS (24.18 +/- 12.73) was lower compared to BD patients who did not have MetS (30.77 +/- 14.45), but this difference was not significant (p > 0.05). Conclusions: Ghrelin levels were lower in BD patients compared to healthy controls. There was no association between reduced ghrelin levels and MetS; however, there was a negative correlation between ghrelin levels and disease activity.
Keywords: Behcet's disease; ghrelin; metabolic syndrome; insulin resistance